Joint Sub-Committee of the T.U.C., the Labour Party and the Co-operative Congress on the Government White Paper "A National Health Service" (minutes) - Labour Party (Great Britain) ; Co-operative Congress
1944-09-05 1944 1940s 6 pages -3- would not obtain preference or priority over public patients The circumstances peculiar to the profession should be recognised and there should be full consultation with the profession on all those matters. We regard medical service, which deals with the lives of the people, as a sacred trust and we are of opinion that the workers in those services, who have necessarily to concern themselves with the troubles of others, should be relieved from financial and other worries so far as the nation can ensure that. It should be definitely laid down that no financial advantage direct or indirect can accrue to a general practitioner as a result of him referring a patient for a second opinion. 5. REHABILITATION We would like to emphasise that no medical service, however well organised or conducted, can be adequate unless it includes a complete, up-to-date, and first class service of rehabilitation as advocated by the Movement for many years. 6. FREEDOM OF CHOICE We agree that within the limits of availability, every individual should have freedom of choice of practitioner whether in separate or in group practice. As doctors will also have freedom of choice of patients, it is essential to provide that such freedom must not operate so as to prevent any individual obtaining all the health care which he needs. 7. CONSULTANTS There are at the present time insufficient consultants and specialists to provide an adequate service and the distribution is uneven. We desire to stress the urgent need to overtake these deficiencies and to express the view that it is of prime importance that the service should attract sufficient men and women of the right type so that in no respect can treatment 292/847/2/10